2020
DOI: 10.3390/jcm9113629
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Combined Extracts of Cornus officinalis and Ribes fasciculatum for Body Fat Reduction in Overweight Women

Abstract: Obesity is a medical condition that presents excessive fat accumulation with high risk of serious chronic diseases. The aim of this clinical trial is to investigate the anti-obesity effects of Cornus officinalis (CO) and Ribes fasciculatum (RF) on body fat reduction in Korean overweight women. A total of 147 overweight female participants enrolled in double-blinded clinical trial for 12 weeks and 76 participants completed the clinical study. Participants were treated with four CO and RF mixture (COEC; 400 mg p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 48 publications
0
6
0
Order By: Relevance
“…In humans, many studies have demonstrated that gender differences are observed in energy consumption, requirements for fat distribution, and metabolism [ 25 ]. Previous studies revealed that CR administration attenuated obesity development in OVX mice [ 18 ], HFD-induced female mice [ 19 ], and women [ 20 ]. Despite the higher prevalence of obesity in women than in men, this study selected HFD-induced obese male mice as an obese animal model as there is a paucity of information on CR effectiveness in males.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In humans, many studies have demonstrated that gender differences are observed in energy consumption, requirements for fat distribution, and metabolism [ 25 ]. Previous studies revealed that CR administration attenuated obesity development in OVX mice [ 18 ], HFD-induced female mice [ 19 ], and women [ 20 ]. Despite the higher prevalence of obesity in women than in men, this study selected HFD-induced obese male mice as an obese animal model as there is a paucity of information on CR effectiveness in males.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, several reports have suggested that RF extract exhibits antiaging effects in Caenorhabditis elegans dependent on the insulin/IGF signaling pathway [ 16 ] and prevents allergic inflammation in LPS-stimulated macrophage cells [ 17 ]. In addition, previous studies have demonstrated that the combination of CO and RF (CR) extract improves estrogenic activity and anti-osteoporotic effects [ 18 ], has along with anti-obesity effects in female mice [ 19 ] and women [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Clinical trials are clearly needed to assess which of the reported pharmacological activities have confirmed efficacy and practical application in humans. (Park et al, 2020e) conducted a randomized, double-blind, controlled trial in Korea and 76 obese female participants were enrolled. The results showed that 12 weeks of administration of the mixture of C. officinalis and Ribes fasciculatum could significantly decrease the body fat of the participants.…”
Section: Discussionmentioning
confidence: 99%
“…Ribes fasciculatum is a plant that grows in East Asia and has been used as a medicinal plant to treat allergies in Korea. According to recent studies, Ribes fasciculatum is known to have anti-obesity, antioxidant, anti-aging, and allergy-relief effects; further, the anti-allergic effect is known to be closely related to cancer cell apoptosis [35][36][37][38][39][40][41][42]. Therefore, we suggest that Ribes fasciculatum has high anticancer bioactivity potential.…”
Section: Introductionmentioning
confidence: 98%